Megakaryocyte and Osteoblast Interactions Modulate Bone Mass and Hematopoiesis - Alvarez, Marta B. (Stem Cells Dev, 2018)
Emerging evidence demonstrates that megakaryocytes (MK) play key roles in regulating skeletal homeostasis and hematopoiesis. To test if the loss of MK negatively impacts osteoblastogenesis and hematopoiesis, we generated conditional knockout mice where Mpl, the receptor for the main MK growth factor, thrombopoietin, was deleted specifically in MK (Mpl(f/f);PF4cre). Unexpectedly, at 12 weeks of age, these mice exhibited a 10-fold increase in platelets, a significant expansion of hematopoietic/mesenchymal precursors, and a remarkable 20-fold increase in femoral midshaft bone volume. We then investigated whether MK support hematopoietic stem cell (HSC) function through the interaction of MK with osteoblasts (OB). LSK cells (Lin(−)Sca1(+)CD117(+), enriched HSC population) were co-cultured with OB+MK for 1 week (1wk OB+MK+LSK) or OB alone (1wk OB+LSK). A significant increase in colony-forming units was observed with cells from 1wk OB+MK cultures. Competitive repopulation studies demonstrated significantly higher engraftment in mice transplanted with cells from 1wk OB+MK+LSK cultures compared to 1wk OB+LSK or LSK cultured alone for 1 week. Furthermore, single-cell expression analysis of OB cultured±MK revealed adiponectin as the most significantly upregulated MK-induced gene, which is required for optimal long-term hematopoietic reconstitution. Understanding the interactions between MK, OB, and HSC can inform the development of novel treatments to enhance both HSC recovery following myelosuppressive injuries, as well as bone loss diseases, such as osteoporosis.